Dynamic Multiprojectile Attack and Killing Effects of Detonation Warheads - Ning Jiang; Wen-Jin Yao; Wen-Bin Li; Wei-Hang Li; Da-Cheng Gao (Shock and Vibration)
Dynamic spatial distribution and killing characteristics of warhead fragments are important topics in the field of weapon effectiveness and protection. However, there is little research on the fragment distribution formed by continuous dynamic attacks of multiple projectiles that explode above the ground. This study analyzes spatial distributions of warhead fragments using witness boards in a rectangular target test. The results show that the fragment distribution of multiple projectiles in continuous dynamic attacks demonstrates a spatial superposition characteristic. The superimposed distribution is the sum of the distributions of two independent fragment distributions. The distribution characteristics are consistent with fragment scattering behavior. Therefore, they can be used to analyze the killing effects of multiple projectiles conveniently. The effects of falling speed, falling angle, and explosion height on the damage range of fragments were explored by a fragment spatial distribution model obtained from experiments. Analysis indicates that the prefabricated fragment distribution conformed to a spatial superposition relationship under dynamic multiprojectile continuous attacks, and the superposition obeyed fragment scattering characteristics. As the projectile falling angle increased at the explosion center, or as the falling height decreased, the positive pressure duration increased gradually. The falling speed had the greatest impact on the specific impulse of overpressure. The falling angle had the greatest impact on the peak value of overpressure. Both the falling angle and the explosion height had the greatest impact on the positive pressure acting time.